Exame de suficiência contábil: Análise crítica do nível cognitivo na perspectiva da Taxonomia de Bloom - Arantes, Daniella Andrade (2019)
The aim of the research is to perform a critical analysis of the cognitive level of the Sufficiency Exam Accounting questions according to the educational objectives from the perspective of the Bloom Taxonomy. In order to achieve this goal, the classification of the Sufficiency Exam Accounting questions according to the six cognitive levels of the taxonomy (knowledge, understanding, application, analysis, synthesis and evaluation) and a validation process of the classification of the questions was carried out. The Evaluation Theory was used to identify and to base in which type of evaluation the Sufficiency Examination (summative, diagnostic or formative evaluation) fits. The skills and competences of the accountant, analyzed in this study, are those provided by the International Federation of Accountants (IFAC) in its IES 3 (International Education Standards 3). The research population consisted of 569 Accounting issues taken from 14 editions of the Examination of Sufficiency (2011.1 to 2017.2). The classification of the questions was validated through a four-step process, through the collaboration of four teachers who are involved in courses in Accounting Sciences, who are familiar with the Bloom Taxonomy. Data were submitted to descriptive analysis. The result of the classification showed that the exam presents low cognitive level, since there are predominance of questions framed in the category less complex - CCA (knowledge, understanding and application). It was therefore concluded that the examination does not adequately explore skills related to the more complex levels of taxonomy, defined as ASA category (analysis, synthesis and evaluation). Considering that the Sufficiency Exam is a certification for professional practice, this study contributes to aggregating information that is useful to the CFC, such as the importance of balancing cognitive categories and diversifying the way of assessment. This research offers a methodological contribution, in the process of validating the classification of questions by specialists and, in addition, brings contributions to higher education institutions, motivating them to follow the changes in the desired professional profile of the accountants, prioritize the development of the cognitive ability and establish clear educational goals. In addition, it contributes to teachers, students and the market, as it enables them to understand how the Examination of Sufficiency is built and whether the CFC considers in its elaboration the skills that future accountants need to develop or improve to act professionally according to accounting practices globally.